2015
DOI: 10.1089/aid.2014.0049
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Outpatient Care for Persons Living with HIV in the United States

Abstract: Prior studies that have assessed engagement within the various stages of care for persons living with HIV (PLWH) studied patients receiving care in HIV medical care facilities. These data are not representative of care received throughout the United States, as not all PLWH receive care in HIV clinics. This study evaluated engagement in outpatient care and healthcare utilization for PLWH, beyond facilities that specialize in HIV. Cross-sectional data were from the 2009-2010 National Hospital Ambulatory Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…The higher prevalence of syphilis testing among older compared to younger MSM has been reported before [12] and may be reflecting age group disparities in retention in continuous HIV care. Studies have shown lower levels of retention in continuous HIV care among HIV-positive adolescent and young adults [19][20][21]. Older MSM in this population may have higher levels of retention in continuous HIV care and have a greater number of interactions with their HIV care provider and more opportunities to be screened for syphilis.…”
Section: Discussionmentioning
confidence: 97%
“…The higher prevalence of syphilis testing among older compared to younger MSM has been reported before [12] and may be reflecting age group disparities in retention in continuous HIV care. Studies have shown lower levels of retention in continuous HIV care among HIV-positive adolescent and young adults [19][20][21]. Older MSM in this population may have higher levels of retention in continuous HIV care and have a greater number of interactions with their HIV care provider and more opportunities to be screened for syphilis.…”
Section: Discussionmentioning
confidence: 97%
“…Limitations to the generalizability and utility of our study findings should be noted. Our clinic population had a median number of 13 visits over 2 years, which far exceeds the threshold definition of engagement in care, usually defined as having 2 visits in a year [ 18 ]. More frequent visits potentially allowed for more reminders that the patient was due for annual HCVAb testing.…”
Section: Discussionmentioning
confidence: 99%
“…5,17,[21][22][23] Studies, however, have also shown that younger persons are less likely to be prescribed ART, which may account for some of the difference seen in our study. [24][25][26][27] Studies have shown mixed results regarding the proportion of persons prescribed ARV drugs, by sex. 2,24,25,27 Both younger persons and women had longer median gap length than older persons and men which may amplify the failure to fill ARV drug prescriptions during these gaps.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Studies have shown mixed results regarding the proportion of persons prescribed ARV drugs, by sex. 2,24,25,27 Both younger persons and women had longer median gap length than older persons and men which may amplify the failure to fill ARV drug prescriptions during these gaps. Persons from the Northeast region also were more likely to never fill an ARV drug prescription during the gap.…”
Section: Discussionmentioning
confidence: 99%